EFFECTIVE TEACHING STRATEGIES FOR ENGLISH LANGUAGE INSTRUCTION IN PRIMARY EDUCATION: THE ROLE OF TEACHER PROFICIENCY - Khaydarova Maftuna Murodilla kizi (Modern American Journals, 2025)
This article explores effective teaching strategies for English language instruction in primary education with a particular focus on the role of teacher proficiency. The research highlights the importance of modern pedagogical approaches in language teaching and demonstrates how teacher knowledge and skills directly affect students’ learning outcomes. Special attention is given to interactive methods, differentiated instruction, games, and project-based learning in fostering communicative competence among young learners. The findings emphasize that enhancing teachers’ professional qualifications plays a decisive role in improving the effectiveness of English language instruction at the primary level.
Keywords: English language teaching, primary education, effective strategies, teacher proficiency, communicative competence, interactive methods, motivation, language learning.